Synthesis and Characterization of an Innovative Polymer Surfactant as a Corrosion Inhibitor for Mild Steel in Hydrochloric Acid - Narjes Ibrahem Khaled; Khitam Zanad Abdul sada; Halah Hameed Majeed; Ahmed Yahya Issa Rubaye (Misan Journal of Engineering Sciences)
Abstract:The co-polymer surfactant, 2-(4-(Methoxy carbonyl)-2,4-dimethyl hexanamido)-2-methyl propane-1-sulfonic acid (M1) at diffident concentrations (250,500,750 & 1000) ppm, was produced and studied structurally by Fourier-transform infrared (FTIR) spectroscopy, 1H NMR, 13C NMR, and elemental analysis. The corrosion inhibition efficacy of M1 on mild steel in 1 M HCl solution was assessed via Potentiodynamic polarization. The results indicated a notable reduction in corrosion rates with different concentrations of M1 at 25°C. M1 attained a corrosion inhibition efficacy of 77.528% at an optimal concentration of 1000 ppm. Tafel polarization investigations indicated that M1 functions as a mixed-type inhibitor, inhibiting both cathodic and anodic processes. The adsorption characteristics of M1 on the mild steel surface were optimally represented by the Langmuir adsorption isotherm, signifying a blend of physical and chemical adsorption mechanisms.